A novel AA14 LPMO from Talaromyces rugulosus with bifunctional cellulolytic/hemicellulolytic activity boosted cellulose hydrolysis - Kaixiang Chen; Xu Zhao; Peiyu Zhang; Liangkun Long; Shaojun Ding (Biotechnology for Biofuels and Bioproducts, 2024)
Abstract Background The recently discovered PcAA14A and B from white-rot basidiomycete Pycnoporus coccineus enriched our understanding of the oxidative degradation of xylan in fungi, however, the unusual mode of action of AA14 LPMOs has sparked controversy. The substrate specificity and functionality of AA14 LPMOs still remain enigmatic and need further investigation. Results In this study, a novel AA14 LPMO was characterized from the ascomycete Talaromyces rugulosus. TrAA14A has a broad substrate specificity with strong oxidative activity on pure amorphous cellulose and xyloglucan. It could simultaneously oxidize cellulose, xylan and xyloglucan in natural hemi/cellulosic substrate such as fibrillated eucalyptus pulp, and released native and oxidized cello-oligosaccharides, xylo-oligosaccharides and xyloglucan oligosaccharides from this substrate, but its cellulolytic/hemicellulolytic activity became weaker as the contents of xylan increase in the alkaline-extracted hemi/cellulosic substrates. The dual cellulolytic/hemicellulolytic activity enables TrAA14A to possess a profound boosting effect on cellulose hydrolysis by cellulolytic enzymes. Structure modelling of TrAA14A revealed that it exhibits a relatively flat active-site surface similar to the active-site surfaces in AA9 LPMOs but quite distinct from PcAA14B, despite TrAA14A is strongly clustered together with AA14 LPMOs. Remarkable difference in electrostatic potentials of L2 and L3 surfaces was also observed among TrAA14A, PcAA14B and NcLPMO9F. We speculated that the unique feature in substrate-binding surface might contribute to the cellulolytic/hemicellulolytic activity of TrAA14A. Conclusions The extensive cellulolytic/hemicellulolytic activity on natural hemi/cellulosic substrate indicated that TrAA14A from ascomycete is distinctively different from previously characterized xylan-active AA9 or AA14 LPMOs. It may play as a bifunctional enzyme to decompose some specific network structures formed between cellulose and hemicellulose in the plant cell walls. Our findings shed new insights into the novel substrate specificities and biological functionalities of AA14 LPMOs, and will contribute to developing novel bifunctional LPMOs as the booster in commercial cellulase cocktails to efficiently break down the hemicellulose-cellulose matrix in lignocellulose.